Multifunctional F-doped TiO2 PCM microcapsules for visible-light-driven photocatalysis and latent heat storage - Zhao, Aiqin (2024)
This paper presented the fabrication of a multifunctional microcapsule, integrating visible-light-driven photocatalysis and latent heat storage capabilities. The core-shell structure incorporated a phase change material in the core, facilitating latent heat storage. Meanwhile the shell was composed of fluorine-doped TiO2, enabling photocatalysis under visible light. Different from conventional fabrication methods necessitating stringent conditions, this study employed a synthesis approach viable at low temperatures (50–90 °C) and ambient pressure. The resulting microcapsule exhibited high photocatalytic capability under visible light, which was able to fully degrade organic dye within 7 h exposure to visible light. Parametric studies indicate photocatalytic efficiency was enhanced with reduced capsule size and elevated fabrication temperature. Optimal conditions were observed at a capsule size of 100 μm and a fabrication temperature of 90 °C. Furthermore, the microcapsule possessed a high thermal storage capacity of 99.4%, indicating the effectiveness of the shell in safeguarding the core material during the phase change process without compromising its energy storage capacity. Even after 100 h of exposure to visible light, the microcapsule demonstrated outstanding thermal stability and durability.